Short‐Term Outcomes of Patent Ductus Arteriosus Closure With New Occlutech® Duct Occluder: A Multicenter Study. (19th April 2016) - Dedeoglu, Reyhan; Bilici, Meki; Demir, Fikri; Demir, Fadli; Acar, Onur Çağlar; Hallioglu, Olgu; Pac, Ayşenur; Kiziltas, Alev; Karabel, Duran; Kula, Serdar; Cimen, Derya; Baspinar, Osman; et al.
Abstract : Aim: Over the past 2 decades, transcatheter occlusion of patent ductus arteriosus (PDA) with coils and the duct occluders evolved to be the procedure of choice. A new device, the Occlutech PDA® occluder (ODO) device has been designed. Herein, we aimed to evaluate the characteristics and short‐term results of patients who underwent transcatheter closure of PDA using the ODO. Methods: We reviewed the clinical records of 60 patients from different centers in Turkey between December 2013 and January 2016. The medical records were reviewed for demographic characteristics and echocardiographic findings. Device size was selected on the narrowest diameter of PDA. Results: The median patient age was 2.5 years (6 months–35 years), and median PDA diameter was 2.5 mm (1.2–11 mm). Fifty‐eight of 60 patients (96.6%) had successful ODO implantation. The occlusion rates were 37/58 (63.7%) at the end of the procedure, 51/58 (87.9%) at 24–48 hours post‐procedure, and 57/58 (98.2%) on echocardiography at a median follow‐up of 7.6 months. Conclusion: Our results indicate that transcatheter closure of PDA using the ODO is effective. Larger studies and longer follow‐up are required to assess whether its shape and longer length make it superior to other duct occluders in large, tubular, or window‐type ducts. (J Interven Cardiol 2016;29:325–331)